ADVOKAT SEBAGAI PILAR PENEGAKAN HAK ASASI MANUSIA: KAJIAN TERHADAP UNDANG-UNDANG NOMOR 18 TAHUN 2003 TENTANG ADVOKAT - Miftah Al Azrin Nainggolan; Muhammad Faiz Abdullah; Afwan Luthfi Pohan; Aji Syahputra Lubis; Aldiansyah H.Siregar (JURNAL ILMIAH NUSANTARA, 2025)
This article discusses the important role of advocates in the Indonesian justice system, especially in the context of providing pro bono legal assistance to underprivileged communities. Since the enactment of Law Number 18 of 2003 concerning Advocates, advocates in Indonesia have been mandated to provide legal assistance without imbalance to individuals or groups who are economically disadvantaged. In addition, Law Number 16 of 2011 concerning Legal Aid further strengthens this obligation by guaranteeing the right to access justice for the poor through the provision of free legal services. The aim of providing legal aid is to ensure that justice can be accessed by all levels of society, regardless of their social or economic status. However, the implementation of this law has not gone without challenges. One of the issues that emerged was the publication of SKMA Number 73/KMA/HK.01/IX/2015 which changed the advocate organization system from "single bar" to "multi bar", which had implications for confusion regarding the authority of advocates in carrying out their profession. Nevertheless, efforts to unite the advocate profession in one organizational forum, in accordance with the mandate of the Advocate Law, continue to be carried out by advocate organizations, especially PERADI. This article emphasizes the importance of establishing a single forum for advocates in order to improve the quality of the profession, strengthen the code of ethics, and ensure that legal aid can be provided more evenly and effectively throughout Indonesia.